2020
DOI: 10.1111/fwb.13667
|View full text |Cite
|
Sign up to set email alerts
|

Do inferences about freshwater phytoplankton communities change when based on microscopy or high‐throughput sequencing data?

Abstract: Microscopy and high‐throughput sequencing (HTS) detect and quantify algae differently. It is not known if microscopy‐based abundance or biomass better compare to HTS data or how methodological differences affect ecological inferences about the phytoplankton communities studied. We investigated methodological (abundancemicroscopy vs. abundanceHTS, biomassmicroscopy vs. abundanceHTS), habitat (littoral, pelagic, deep hypolimnion), and year (2014 vs. 2017) differences for phytoplankton communities of Lake Tovel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 107 publications
6
6
0
Order By: Relevance
“…Among genera, 36–55% were identified by both methods, while for species 9–27%, common identifications were found. These results are in agreement with previous reports on freshwater phytoplankton, where only a few common taxa were found by microscopy and metabarcoding operational taxonomic units (OTUs). ,, …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Among genera, 36–55% were identified by both methods, while for species 9–27%, common identifications were found. These results are in agreement with previous reports on freshwater phytoplankton, where only a few common taxa were found by microscopy and metabarcoding operational taxonomic units (OTUs). ,, …”
Section: Discussionsupporting
confidence: 93%
“…The biodiversity of eukaryotic nano-and microphytoplankton showed higher values for metabarcoding than for microscopy (Figure 2). This is in agreement with some earlier studies, 16,27 but a recent meta-analysis of marine and freshwater environments showed rather similar alpha diversity of plankton and microphytobenthos for microscopy compared to DNA metabarcoding. 28 Furthermore, a previous study reported that traditional microscopy identified more taxa than metabarcoding for certain phyla, for example, Cryptophyta and Dinophyta.…”
Section: ■ Materials and Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Whereas this method can provide quantitative estimates of phytoplankton biomass and composition at high taxonomic resolution (down to morphospecies level), it is also time-consuming, requires expert taxonomic knowledge that is not generally available, and often fails to properly include the picophytoplankton (Paerl, 1978;Culverhouse et al, 2003). Two alternative approaches promising faster, cost-efficient and potentially more comprehensive assessment of phytoplankton community composition are high-throughput amplicon sequencing (HTS) of taxonomically diagnostic DNA sequences (Baird & Hajibabaei, 2012;Caron, 2013;Eiler et al, 2013;Abad et al, 2016;Keck et al, 2017;Pawlowski et al, 2018;Obertegger et al, 2020) and high-performance liquid chromatography (HPLC) of photosynthetic marker pigments (Jeffrey et al, 1997(Jeffrey et al, , 1999Descy et al, 2000Descy et al, , 2005Sarmento et al, 2006;Lauridsen et al, 2011). Both methods allow the simultaneous processing of multiple samples, and can detect small and fragile phytoplankton taxa that are often overlooked by microscopy.…”
Section: Introductionmentioning
confidence: 99%